Treatment of depression in older adults beyond fluoxetine - Gabriela Arantes Wagner (Universidade de São Paulo, 2015)
This review aimed to discuss the importance of the comprehensive treatment of depression among older adults in Brazil. The abuse of selective serotonin reuptake inhibitors, including fluoxetine hydrochloride, as antidepressants has been considered a serious public health problem, particularly among older adults. Despite the consensus on the need for a comprehensive treatment of depression in this population, Brazil is still unprepared. The interface between pharmacotherapy and psychotherapy is limited due to the lack of healthcare services, specialized professionals, and effective healthcare planning. Fluoxetine has been used among older adults as an all-purpose drug for the treatment of depressive disorders because of psychosocial adversities, lack of social support, and limited access to adequate healthcare services for the treatment of this disorder. Preparing health professionals is a sine qua non for the reversal of the age pyramid, but this is not happening yet.